Subsurface drainage technology for restoring crop productivity in waterlogged saline soils - Vibhute, Sagar D.; Kumar, Satyendra; Bundela, D. S.; Kumar, Suresh; Chinchmalatpure, Anil R.; Kumar, Jitendra; Narjary, Bhaskar; Mukhopadhyay, Raj; Pathan, Aslam L. (Indian Farming, 2025)
Waterlogged saline soils are severely affecting crop production in irrigated areas of the country and appropriate technologies need to be adopted for their reclamation. Subsurface drainage (SSD) is proven technology for reclamation of such soils and about 1,10,000 ha area has been reclaimed in India using this technology. However, very high installation cost, non-availability of adequate trencher machines and need of region/soil specific design requirements has resulted in its adoption at very slow pace. The brief information of SSD technology covering its benefits, components, installation, and a few case studies of its performance in different parts of the country is presented in this article.